(untitled) (Sociologisk Forskning, 2023)
Climate change leads to increased and new risks in societies. Pluvial flooding is one such risk that already generates major damages, which are expected to increase significantly in the future. Not least, many homeowners risk being affected by floods, and have been attributed a central role in Sweden’s climate adaptation policy. Despite this, no previous Swedish studies have specifically investigated how homeowners have been affected by floods beyond damage costs, and few studies have investigated how homeowners have managed or view their responsibility to prevent pluvial flood risks. The lack of such knowledge may lead to less informed decisions about climate adaptation. Through interviews with homeowners affected by flooding, this study examines how they; experience flood risks, have been affected materially and health-wise, have managed the situation, and consider responsibility to prevent new damage. The study shows clear effects on the well-being of homeowners, that few have adapted their property and tend to underestimate the flood risk facing their property. Homeowners also tend to displace responsibility for preventive measures to other actors, mainly the municipality.